Applications of the Finite Operator〖 〗_3 E_2 (■(q^(-N),a,b@c,d);q,-fθ) for the Polynomials B_n (a,b,c,d,f,x,y|q) - Jaber, Rasha H.; Saad, Husam L. (Iraqi Journal of Science, 2023)
In this work,   polynomials  and the finite q-exponential operator  are constructed. The operator  is used to combine an operator proof of the generating function with its extension, Mehler's formula with its extension and Roger's formula for the polynomials . The generating function with its extension,  Mehler's formula with its extension and Rogers formula for Al-Salam-Carlitz polynomials  are deduced by giving special values to polynomials .